Health promotion model based community nursing for improving psychological well-being and treatment adherence among patients with hypertension - Juanda Sitepu; Cau Kim Jiu; Lidia Hastuti (JOURNAL OF Mental Health Concerns, 2026)
Background: Hypertension is one of the most prevalent non-communicable diseases in Indonesia, with a prevalence rate of 34.1% in 2023. At Silat Hilir Primary Health Center, Kapuas Hulu Regency, West Kalimantan, adherence to antihypertensive medication is only 43%, far below the 70% target established by the Minimum Service Standards (MSS). This gap is exacerbated by geographical barriers in remote rural areas, limited health literacy, and the absence of a structured community-based monitoring system. Purpose: To improve psychological well-being and treatment adherence among patients with hypertension through the implementation of “BAKSO CERDIK”, an innovative community nursing approach based on the Health Promotion Model (HPM). Method: This article presents a community nursing innovation paper using a descriptive-analytic approach. Program development was based on evidence synthesized from a systematic literature review (2014–2024) and an analysis of the local epidemiological situation. The theoretical framework was derived from Pender’s Health Promotion Model (1982, revised 2011), which was operationalized through two complementary pillars: “BAKSO” (Bina-Awasi-Kontrol-Support-Observasi) for medication adherence monitoring and “CERDIK” (Cek-Enyahkan-Rajin-Diet-Istirahat-Kelola) for healthy lifestyle promotion. Results: The program is implemented by trained community health cadres through a monthly cycle integrated into the Integrated Primary Care (ILP) system of the Primary Health Center. Based on evidence from the literature, the program is projected to increase medication adherence from 43% to ≥70%, improve blood pressure control rates from 30% to ≥60%, and reduce treatment dropout rates by up to 50% within the first year of implementation. Conclusion: The intervention is a theoretically grounded, contextually relevant, and systemically integrated community nursing innovation that addresses the gap between high service coverage and low treatment adherence through proactive community-based interventions aligned with the national ILP policy and hypertension MSS targets. Keywords: Health Promotion Model; Psychological Well-Being; Treatment Adherence.